Determination of electric characteristics of a high-frequency torch discharge; Thermophysics and Aeromechanics; Vol. 15, № 1 - Vlasov V. A. Viktor Alekseevich (2008, 2008)
Electric characteristics of a high-frequency torch discharge measured by the resonance method are presented. It is shown that discharge capacity determined by the modified Neumann scheme is close to the value of electrostatic capacity. Capacity of discharge channel was calculated with consideration of propagation of a surface electromagnetic wave along this channel/